Pendidikan Pesantren Berperspektif Gender: Gender Perspective in Islamic Boarding School Education - St. Mislikhah (LP2M Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember, 2007)
Islamic boarding schools (pesantren) in Indonesia have strategic potential as agents of social change, yet many still perpetuate patriarchal norms and gender bias in their curricula and teaching methods. This study describes how gender-perspective education is implemented at Pondok Pesantren Nurul Islam Jember, focusing on the curriculum and learning methodologies. A qualitative case study approach was employed, using observation, in-depth interviews, and documentation. Data were analyzed using an interactive model involving data reduction, display, and verification, with credibility ensured through extended observation and triangulation. The findings reveal that a gender perspective is integrated into the pesantren curriculum, although no standalone gender subject exists. Gender messages are embedded in classical kitab kuning studies, while role modeling and gender mainstreaming are practiced in daily activities. Learning methods such as sorogan, bandongan, and memorization are adapted to encourage critical thinking, avoid segregation, and provide equal opportunities for male and female students. The study concludes that gender-responsive education at Nurul Islam is viable through curriculum integration, egalitarian role modeling, and inclusive pedagogy. Recommendations include formalizing gender materials and providing continuous teacher training to sustain institutional transformation toward gender justice. Pesantren di Indonesia memiliki potensi strategis sebagai agen perubahan sosial, namun banyak di antaranya masih melestarikan norma patriarkhi dan bias gender dalam kurikulum serta metode pembelajarannya. Penelitian ini bertujuan mendeskripsikan penerapan pendidikan berperspektif gender di Pondok Pesantren Nurul Islam Jember, khususnya pada kurikulum dan metodologi pembelajaran. Pendekatan kualitatif dengan studi kasus digunakan, melalui observasi, wawancara mendalam, dan dokumentasi. Analisis data model interaktif meliputi reduksi, penyajian, dan verifikasi data, dengan uji kredibilitas melalui perpanjangan pengamatan dan triangulasi. Hasil penelitian menunjukkan bahwa kurikulum berperspektif gender diintegrasikan ke dalam materi kitab kuning tanpa mata pelajaran khusus. Pesan-pesan gender disisipkan dalam pembelajaran, keteladanan perilaku responsif gender diberikan, dan pengarusutamaan gender dilakukan dalam seluruh aktivitas. Metode sorogan, bandongan, dan hafalan disesuaikan untuk mendorong berpikir kritis, tanpa segregasi, serta memberikan kesempatan setara bagi santri laki-laki dan perempuan. Kesimpulannya, pendidikan responsif gender di pesantren dapat diwujudkan melalui integrasi kurikulum, keteladanan, dan metode inklusif. Rekomendasi mencakup formalisasi materi gender dan pelatihan berkelanjutan bagi pengajar.